2014
DOI: 10.1080/15389588.2014.895924
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bicycle Oriented Facilities on Bicycle Crashes within Crash Concentrated Areas

Abstract: This study presents guidelines for local transportation planners to analyze the patterns of bicyclist crashes in order to improve roadway safety. This research also assists planners in effectively allocating scarce resources as they address issues of bicyclist safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…For instance, at night, a road can be less congested which, in turn, let the driver operate at faster speed (Liu et al, 1995), thereby increasing the likelihood of a BMV collision. Moreover, another study, by contrast, has demonstrated that street light conditions did not have a significant impact on the likelihood of BMV collisions (D. Kim & Kim, 2015).…”
Section: Environmentmentioning
confidence: 90%
See 3 more Smart Citations
“…For instance, at night, a road can be less congested which, in turn, let the driver operate at faster speed (Liu et al, 1995), thereby increasing the likelihood of a BMV collision. Moreover, another study, by contrast, has demonstrated that street light conditions did not have a significant impact on the likelihood of BMV collisions (D. Kim & Kim, 2015).…”
Section: Environmentmentioning
confidence: 90%
“…A distance of 2-5m between the cycle track (see supplemental material) and the side of the main carriageway decreased the risk of collision (Schepers et al, 2011). Concerning the importance of separation, another study found that the quantity of unclear borders (e.g., defined separation of space by a physical barrier) was associated with increased risk of BMV collisions (D. Kim & Kim, 2015). A defined separation of space by a physical barrier can reduce the invasion of sidewalks by motorized vehicles.…”
Section: Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…From the infrastructure perspective, the presence of cycling facilities (e.g., Aultman-Hall and Hall 1998;Pucher et al 1999) is related to an increase in the crash rates of cyclists, although recent evidence contradicts initial findings and proclaims bicycle lanes as safer (de Rome et al 2014;Kaplan et al 2014). Also, higher numbers of light injuries among cyclists are recorded in proximity of parking facilities and public transport stops (e.g., Kim et al 2007; Kim and Kim 2014;Rifaat et al 2011). From the traffic condition perspective, both peak and off-peak hours observe less crashes (e.g., Hels and Orozova-Bekkevold 2007;Wang and Nihan 2004), but the severity is lower in peak hours because of the reduced speed differential between fast and slow transport modes and higher in off-peak hours because of high vehicle speeds (e.g., Kaplan et al 2014;Kim et al 2007; Klop and Khattak 1999).…”
Section: Introductionmentioning
confidence: 94%